The impact of environment on human religiosity: The possibility of piety in a culture of meaninglessness and mutual "passing-by" - Dizdarević Bajram (Kom: Časopis za Religijske Nauke)
Since each person is essentially immersed in his own context, that is, the time and space in which he lives, and that he cannot think outside of that context about the phenomena that occur in that time, and that the upbringing (adab) of a person significantly determines his relationship to social conditions, in this paper, we will concentrate on how the urban or rural environment affects the spiritual or intellectual growth of a person, and whether the rural environment in which primordiality is emphasized strengthens the qualitative growth of that very dimension (fiṭrah) in a person, i.e. whether the urban environment that is overwhelmed by handiwork, i.e. by an all-too-human ambience, suffocates it, and prevents its true actualization. In addition to the aforementioned, we plan to examine whether it is even possible to be religious in the city environment, since the modern city is characterized by deep ontological nothingness and Kafkaesque nonsense, and what are the consequences of the almost complete fusion of the village and the city, as a result of which it is no longer possible to count on a gradual cultural-civilization the maturing of the people, i.e. the intellectual and spiritual growth of individuals.